Magnetic Anisotropy and Microstructure in Electrodeposited Quaternary Sn-Fe-Ni-Co Alloys with Amorphous Character - Ernő Kuzmann (Materials, 2022)
Sn-Fe-Ni-Co quaternary alloys, in the composition range of 37–44 at% Sn, 35–39 at% Fe, 6–8 at% Ni and 13–17 at% Co, were prepared by direct current (DC) and pulse plating (PP) electrodeposition. The alloy deposits were characterized by XRD, 57Fe and 119Sn conversion electron Mössbauer spectroscopy, SEM-EDX and magnetization measurements. XRD revealed the amorphous character of the quaternary alloy deposits. The dominant ferromagnetic character of the deposits was shown by magnetization and Mössbauer spectroscopy measurements. Room temperature Mössbauer spectra showed minor paramagnetic phases, where their occurrences (~3–20%) are correlated to the electrodeposition parameters (Jdep from −16 to −23 mA/cm2 for DC, Jpulse from −40 to −75 mA/cm2 for PP), the composition and the saturation magnetization (~52–73 emu/g). A considerable difference was found in the magnetization curves applying parallel or perpendicular orientation of the applied fields, indicating magnetic anisotropy both in DC and pulse plated alloy coatings.